Effects of reaction temperature and reaction time on the hydrothermal liquefaction of demineralized wastewater algal biomass. (June 2021) - Carpio, Rowena B.; Zhang, Yuanhui; Kuo, Chih-Ting; Chen, Wan-Ting; Schideman, Lance Charles; de Leon, Rizalinda
Abstract: Hydrothermal liquefaction (HTL) of demineralized wastewater algal biomass was studied under different reaction temperatures (260–320 °C) and time (0–90 min). A moderate reaction condition (280 °C, 60 min) was found sufficient to produce the highest oil yield ( 26% daf). Analysis of this oil showed a potential distillation recovery of 71% at 400 °C (mostly in the jet fuel to fuel oil range). All oils obtained have a comparable HHV (35.20–36.76 MJ/Kg) similar to tar (36 MJ/kg). GC–MS analysis showed that the oils derived are comparable, except at extreme reaction conditions (320 °C, 60 min) where a better fuel component in terms of hydrocarbons and N&O-heterocyclic compounds was achieved. The energy consumption ratio (ECR) of oils from demineralized biomass (0.37–0.45) is 80–120% lower compared to that of untreated biomass (ECR = 0.85) at 300 °C and 60 min. Graphical abstract: Unlabelled Image Highlights: First work on HTL of demineralized algal biomass at different reaction conditions. Biocrude oil produced is mostly in the jet fuel to fuel oil range. Oil production from HTL of demineralized algal biomass is energetically feasible. Extent of deoxygenation and denitrogenation affected by reaction conditions.